Enhanced Production and Characterization of a Solvent Stable Amylase from Solvent Tolerant Bacillus tequilensis RG-01: Thermostable and Surfactant Resistant - Soni Tiwari; Neha Shukla; Pooja Mishra; Rajeeva Gaur (The Scientific World Journal)
Ten bacterial strains isolated from the soil samples in the presence of cyclohexane were screened for amylase production. Among them, culture RG-01 was adjudged as the best amylase producer and was identified as Bacillus tequilensis from MTCC, Chandigarh. The isolate showed maximum amylase production (8100 U/mL) in the presence of starch, peptone, and Ca2+ ions at 55°C pH 7.0 within 24 h of incubation. The enzyme was stable in the presence of n-dodecane, isooctane, n-decane, xylene, toluene, n-hexane, n-butanol, and cyclohexane, respectively. The presence of benzene, methanol, and ethanol marginally reduced the amylase stability, respectively. The enzyme was showed it 100% activity at 55°C and pH 7.0 with 119% and 127% stability at 55°C and pH 7.0, respectively. The enzyme was also stable in the presence of SDS, Tween-40, Tween-60, and Tween-80 (1%) and was found stimulatory effect, respectively. Only Triton-X-100 showed a moderate inhibitory effect (5%) on amylase activity. This isolate (Bacillus tequilensis RG-01) may be useful in several industrial applications owing to its thermotolerant and organic solvents and surfactants resistance characteristics.